Control of a Modular Multilevel Matrix Converter for Unified Power Flow Controller Applications - Chavez-Orostica, H; Rojas-Lobos, F; Diaz-Diaz, M; Ibaceta-Valenzuela, E; Duran-Sepulveda, A (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The modular multilevel matrix converter has been proposed as a suitable option for high power applications such as flexible AC transmission systems. Among flexible AC transmission systems, the unified power flow controller stands out as the most versatile device. However, the application of the modular multilevel matrix converter has not been thoroughly analyzed for unified power flow controller applications due to the sophisticated control systems that are needed when its ports operate at equal frequencies. In this context, this paper presents a cascaded control structure for a modular multilevel matrix converter based unified power flow controller. The control is implemented in a decoupled reference frame, and it features proportional-integral external controllers and internal proportional multi-resonant controllers. Additionally, the input port of the modular multilevel matrix converter is regulated in grid-feeding mode, and the output port is regulated in grid-forming mode to provide power flow compensation. The effectiveness of the proposed vector control system is demonstrated through simulation studies and experimental validation tests conducted with a 27-cell 5 kW prototype. © 2020 by the authors.